Concepts for external light trapping and its utilization in colored and image displaying photovoltaic modules. (3rd February 2017) - van Dijk, Lourens; van de Groep, Jorik; Veldhuizen, Leon W.; Di Vece, Marcel; Schropp, Ruud E. I.
Abstract: The reflection of incident sunlight prevents photovoltaic modules from reaching their full energy conversion potential. Recently, we demonstrated significant absorption enhancement in various solar cells by external light trapping, using 3D‐printed and milled light traps. In order to facilitate direct module integration, we introduce an external light trapping design concept tackling the reflection issues at the module level. In this module design, a lens array on the module cover glass funnels the incident sunlight through small apertures in a reflective coating at the backside of the cover glass. This adapted cover glass can be applied on a conventional module design. The reflector and the solar cells together form an optical cavity, in which most reflected light is recycled by directing the reflected light back to the solar cell. A unique feature of this light trapping module is its capability to simultaneously recycle the broadband reflection from the metal front grid, the front interfaces, the reflective backside of the cell, and the white back sheet. Moreover, it allows separate integration and contacting of low and high bandgap solar cells for highly efficient hybrid tandem modules that have no current matching related losses. We show five module designs for improved light management combined with additional features such as color and image display. We discuss the optimal harvesting of the diffuse and direct component of the sunlight. The outlook of highly efficient, colored, and even image displaying modules makes this technology an interesting candidate for a new class of photovoltaic modules. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We introduce a design of a light trapping module that recycles the reflected light and thereby improves the module power conversion efficiency. A lens array on the module cover glass directs the incident sunlight through small apertures in a reflective coating at the backside of the cover glass. The outlook of highly efficient, colored, and even image displaying modules makes this technology an interesting candidate for a new class of photovoltaic modules.